Differences in gender and performance in off-road triathlon - Lepers, R.; Stapley, P. J. (Journal of Sports Sciences, 2010)
The aims of this study were: (1) to examine performance trends and compare elite male and female athletes at the off-road triathlon (1.5-km swim, 30-km mountain biking, and 11-km trail running) world championships since its inception in 1996, and (2) to compare gender-related differences between off-road triathlon and conventional road-based triathlon. Linear regression analyses and ANOVA were used to examine performance trends and differences between the sexes. Elite male performance times stabilized over the 2005-2009 period, whereas elite female performance times continued to improve, especially for the run leg. Differences in performance times between the sexes were less marked in swimming than in mountain biking and running, whereas differences in power output were more marked for mountain biking than for swimming and running. In addition, differences in cycling between the sexes were greater for off-road than conventional on-road triathlon. The specific aspects of mountain biking (e.g. level and terrain) may partly explain the significant differences between the sexes recorded in cycling for off-road triathlon. Future studies will need to focus on the physiological bases of off-road triathlon and how they differ from conventional triathlon.